Analysis of miRNA expression patterns in human and mouse hepatocellular carcinoma cells2. Issue 13 (7th April 2015) - Baek, Sinhwa; Cho, Kyung Joo; Ju, Hye‐Lim; Moon, Hyuk; Choi, Sung Hoon; Chung, Sook In; Park, Jun Yong; Choi, Ki Hong; Kim, Do Young; Ahn, Sang Hoon; Han, Kwang‐Hyub; Ro, Simon Weonsang
Abstract : Aim: Hepatocellular carcinoma (HCC), one of the most common malignancies in adults displays aberrant miRNA expression during its pathogenesis. We assessed expression of miRNA in surgically resected human HCC of an early stage and murine HCC with a high malignancy in order to find miRNA overexpressed in HCC regardless of tumor stage and underlying etiology. Further, the role of the deregulated miRNA in HCC pathogenesis was investigated. Methods: miRNA were isolated from HCC tissues and surrounding non‐tumorous tissues from HCC patients and a murine transgenic model of HCC. A quantitative reverse transcription polymerase chain reaction was performed to determine expression levels of miRNA. Human HCC cell lines stably expressing individual miRNA were generated to investigate the biological function of overexpressed miRNA. Results: We found that levels of miR‐221, ‐181b‐1, ‐155‐5p, ‐25 and ‐17‐5p were significantly upregulated in both human and murine HCC regardless of tumor stage, underlying etiology or the presence of fibrosis. Using HCC cell lines stably expressing respective miRNA, we found that miR‐221 increased the proliferation of hepatoma cells, while miR‐17‐5p induced cell migration. Conclusion: We identified miRNA that are consistently upregulated in HCC. The overexpressed miRNA could potentially be used as a bona fide biomarker for HCC.